Assessing the financial viability of growing industrial hemp with loblolly pine plantations in the southeastern United States - Barnes, Thomas; Parajuli, Rajan; Leggett, Zakiya; Suchoff, David (Frontiers in Forests and Global Change, 2023)
Industrial hemp (Cannabis sativa L. <0.3% THC), a non-psychoactive chemotype of cannabis, was reclassified and made legal for growing across the United States under the 2018 Farm Bill. Given that resources, knowledge, and interest for this novel crop are expanding rapidly, we explored the possibility of intercropping industrial hemp for fiber with loblolly pine (Pinus taeda) plantations, one of the most commercially widespread tree species in the southern United States. Following a previous greenhouse study confirming hemp’s ability to grow in pine-influenced soils, we examined the financial feasibility of this potential agroforestry system. We simulated the loblolly pine tree growth information using PTAEDA 4.0, a growth and yield model, and collected the enterprise budget data on hemp productivity, operating and fixed costs, and prices from various sources. Based on the capital budgeting analyses, results suggest that pine-hemp intercropping can yield higher economic returns –at least 25% higher net present value—than the conventional monoculture loblolly pine plantation. The early rotation cash flow and the complimentary benefits can result in a more financially viable loblolly pine plantation under the intercropping scenario. While new research continues to advance further with field trials and other analyses, this study provides valuable insights into the current market conditions and productivity level of industrial hemp cultivation that need to be addressed for hemp intercropping to succeed as an economically viable agroforestry investment.